ANALYZING THE STUDENTS’ LISTENING ABILITY ON ENGLISH SONG OF THE SECOND YEAR STUDENTS OF SMA NEGERI NOEMUTI TIMUR - Rinciana Naisali; Imanuel Kamlasi (STKIP PGRI Jombang, 2021)
AbstractThis study aims at finding out level is the students listening ability on English Song categorized and at describing the difficulties faced by the students in listening ability on English Song. Therefore, this writer applied listening test. The method used in this research is descriptive qualitative. There are 10 students taken to do the test. The writer use two items for measuring; missing word and multiple choice. The results showed that the students' listening ability toward songs reached a minimum standard of completeness (83%). Then from research testing conducted by the author shows that the ability to listen of the second year in SMA Negeri Noemuti Timur can reach the minimum standard of achievement (83%) using songs because the songs are easy for students to improve their listening abilities. The data shows that there are 10 students attended in the listening test and all the past in the test. The students have mastered listening using English Songs in the missing word. The students’ average score is 81% and the level of ability is very good. The students have mastered listening using English songs in the Multiple Choice test. The student’s average score is 85% and the level of ability is very good. Keywords : Listening, Ability, English Song.